Perkembangan Khidmat Ilmiah Terhadap Hadis-hadis Al-tib Al-nabawi: Analisis Sistematik - Muhammad Akmalludin Mohd Hamdan; Mohd Zahir Abdul Rahman; Muhammad Sobri Faisal (Universiti Sains Islam Malaysia, 2024)
Journal Of Hadith Studies, Volume 8 Issue 2 Page (145-158)